Disruptive Norms: Assessing the Impact of Ethnic Minority Immigration on Nonimmigrant Voter Turnout Using a Complex Model. (August 2020) - Loughran, Thomas; Fieldhouse, Edward; Lessard-Phillips, Laurence; Bentley, Lee
This article explores whether introducing an external group into a population with different characteristics to the existing population may lead to behavioral change. Specifically, we test whether introducing ethnic minority immigrants with varying levels of civic duty (commitment to voting) norms into a previously homogenous nonimmigrant ethnic majority population influences voter turnout among the nonimmigrant majority group. The findings have been produced using a complex agent-based model ("the voter model") where the parameters and characteristics have been developed through the extensive synthesis of existing findings from real-world social science research on voter turnout. The model adopts the KIDS ("Keep It Descriptive Stupid") approach to this form of modeling complex systems. The model puts a particular emphasis on exploring the dynamic social aspects that influence turnout by focusing on the role of networks and spatial composition factors such as ethnic diversity and levels of internal and external immigration. It uses an approach based on aggregative neighborhood dynamics to go beyond existing static models of the influence of social norms on voting similar to the classic approach of Schelling. The main findings from this article suggest that, other factors being equal, increased levels of immigration lead to a small but significant increase in turnout among the nonimmigrant population and show that higher levels of civic duty among immigrants lead to higher levels of turnout among nonimmigrants over time. This challenges the popular belief that increased immigration and diversity in a specific community will always lead to lower turnout levels.